AB1242 A NOVEL BIOMARKER OF MMP-CLEAVED PROLARGIN IS ELEVATED IN PATIENTS WITH PSORIATIC ARTHRITIS COMPARED TO OTHER FIBRO-INFLAMMATORY DISEASES. (2nd June 2020) - Sinkeviciute, D.; Schlemmer, A.; Berg Schmidt, E.; Bay-Jensen, A. C.; Karsdal, M.; Hagstrup Christensen, J.; Kristensen, S.; Holm Nielsen, S.
Abstract : Background: Psoriatic Arthritis (PsA) is a chronic inflammatory disease, characterized by involvement of skin, axial and peripheral skeleton. Prolargin is a class II small leucine-rich proteoglycan found to be expressed in connective tissues of patients with PsA, and previously suggested to be remodelled upon treatment. Fragments of prolargin could quantify tissue turnover in individuals with PsA and reflect pathological tissue changes in these patients. Objectives: This study aimed at developing an immunoassay targeting a neo-epitope of prolargin cleaved by matrix metalloproteinases (MMPs), named PROM; and measure PROM levels in serum from two cohorts of patients affected by PsA and healthy controls. Methods: Development of a novel immunoassay targeting a specific MMP-generated neo-epitope fragment of prolargin (PROM) together with technical validation was performed, and then evaluated in serum from two independent cohorts. The technical validation included inter- and intra-variation, linearity, spiking recovery, stability and specificity. Specificity was tested using an elongated peptide, a truncated peptide and a non-sense peptide. The Discovery Cohort consists of 13 healthy individuals and 11 PsA patients, mean age 58, 60.3% female and 100% caucasian. The Validation Cohort included 35 healthy individuals and 112 PsA patients with low disease activity included in a 24-week randomized, double-blind, placebo-controlled trial of 3g n-3 polyunsaturated fatty acids (PUFA), a cohort of patients diagnosed with PsA by the CASPAR criteria. These patients had a mean age of 50.8, 57.8 % female and 100 % caucasian. Clinical variables and serum samples were collected at baseline and after 24 weeks of follow-up. An unpaired t-test was used for evaluation of healthy individuals and patients affected by PsA, while a paired t-test was used for evaluation of treatment at baseline and after 24 weeks. Results: A technically robust and specific assay was developed. The inter- and intra-assay variation of PROM was determined as 14% and 4 % respectively. PROM showed a good dilution recovery, spiking recovery, and storage /freeze-thaw stability (All, 100%±20%). PROM showed to be specific towards the targeted sequence, and did not show any reactivity towards the truncated peptide, elongated peptide or non-sense peptide. In the Discovery Cohort, serum levels of PROM were increased in patients with PsA compared to healthy individuals (p=0.032, Figure 1A ). This increase was confirmed by the Validation Cohort, where PsA patients were significantly increased compared to healthy individuals at baseline (p=0.002, Figure 1B ). After 24 weeks, the levels of PROM were unchanged in the n-3 PUFA treated group. Conclusion: The novel biomarker PROM, reflecting connective tissue remodeling, is elevated in PsA patients compared to healthy controls in two independent cohorts. No significant association was found for PROM in a low disease activity group of PsA patients treated with n-3 PUFA. References: None Acknowledgments: We thank the Innovation Foundation and Danish Research Foundation for providing funding for this study. Disclosure of Interests: Dovile Sinkeviciute Grant/research support from: Industrial PhD Student, Employee of: Industrial PhD Student, Annette Schlemmer: None declared, Erik Berg Schmidt: None declared, Anne-Christine Bay-Jensen Shareholder of: Nordic Bioscience A/S, Employee of: Full time employee at Nordic Bioscience A/S., Morten Karsdal Shareholder of: Nordic Bioscience A/S., Employee of: Full time employee at Nordic Bioscience A/S., Jeppe Hagstrup Christensen: None declared, Salome Kristensen: None declared, Signe Holm Nielsen Employee of: Full time employee at Nordic Bioscience